The Effect of Pulmonary Rehability on Critical Walk Speed in Patients with COPD: A Comparison with Self-Paced Walks - Dolmage, T.; Evans, R.; Hill, Kylie; Blouin, M.; Brooks, D.; Goldstein, R. (American College of Chest Physicians, 2011)
Background: Walking is frequently used in the exercise rehabilitation of patients with COPD. Walking ability can be characterized by the two-parameter hyperbolic relationship between endurance and speed. One parameter, critical walk speed (s_critical), represents the maximum speed that can be endured indefinitely. The purpose of this study was to: (1) determine the effect of pulmonary rehabilitation on the critical speed and (2) compare the critical speed with the speed chosen during self-paced walking. Methods: We estimated critical speed in patients with COPD before and after rehabilitation. Patients completed four high-intensity constant-speed walk tests to intolerance on a 30-m course. The parameters of the hyperbolic relationship were determined using nonlinear regression of endurance on speed. Participants also completed self-paced walks: (1) for as long as they could, (2) at their “usual” and “fast” speeds, and (3) as a 6-min walk test. Results: Twelve participants (FEV1 [SD], 41 [16] % predicted; FEV1/FVC, 41 [12]) completed the study. At baseline, the critical speed (65 [12] m/min) was not significantly different from the self-paced, usual, or 6-min walk speeds (65 [12], 67 [14], and 63 [15] m/min, respectively). There was a significant increase in critical speed (6 [1-10] m/min) and 6-min speed (16 [10-21] m/min) after rehabilitation, without changes in the self-paced, usual, or fast speeds. Conclusions: Patients with COPD increase their critical walk speed after pulmonary rehabilitation. The pace chosen during common walk tasks is closely related to critical speed; this relationship is altered after rehabilitation.